Describing healthcare providers' perceptions of relational practice with families in the emergency department: A qualitative study - Waheedha Emmamally; Christen Erlingsson; Petra Brysiewicz (AOSIS, 2020)
Background: Emergency departments are regarded as stressful working environments, associated with staff shortages, increased patient numbers and long waiting times. Increased organisational demands for performance can compromise genuine interactions between families and healthcare providers working in emergency departments. A relational practice approach in caring for families can enhance the capability of healthcare providers to simultaneously overcome these difficulties and provide emergency healthcare of high quality. Objectives: The purpose of the study was to describe healthcare providers' perceptions of relational practice with families in three emergency departments in KwaZulu-Natal, South Africa. Method: Using a qualitative descriptive approach data were collected through semi-structured interviews with healthcare providers working in emergency departments. The data were analysed and categorised using qualitative content analysis. Results: Four categories emerged from data analysis: (1) families and healthcare providers connecting; (2) recognising the uniqueness of families; (3) caring interactions; and (4) taking charge when necessary. Conclusion: The study elicited that healthcare providers working in emergency departments perceived that despite high patient volumes and resource constraints, collaborative relationships with families were important. However, these collaborative relationships cannot be willed into practice, instead training workshops are needed to develop relational skills of healthcare providers which can facilitate family and healthcare professional collaboration.